A pooled analysis of individual patient data from registrational trials of silodosin in the treatment of non‐neurogenic male lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH). (13th March 2014) - Novara, Giacomo; Chapple, Christopher R.; Montorsi, Francesco
<x xml:space="preserve">Abstract</x> Objective To evaluate the efficacy and safety of silodosin in a pooled analysis based on individual patients data from three randomised controlled trials (RCTs) comparing silodosin and placebo. Patients and methods A pooled analysis of 1494 patients from three 12‐week, similarly designed, parallel‐group, multicentre, randomised, double‐blind, placebo‐controlled phase III RCTs (SI04009, SI04010, KMD3213‐IT‐CL 0215) was performed. Differences from placebo for the mean change from baseline to the end of treatment for the International Prostate Symptom Score (IPSS) and uroflowmetry data were tested using an analysis of covariance model. Results At study end, in the intention‐to‐treat population, silodosin was significantly more effective than placebo in improving IPSS total score (adjusted means differences [AMD] 2.7; P < 0.001). Silodosin was significantly more effective than placebo in improving storage, voiding, and quality‐of‐life‐item subscores (all P < 0.001). Similarly, silodosin was more effective than placebo in improving maximum urinary flow rate (Qmax; AMD 0.8; P = 0.002). The most frequently reported adverse event (AE) was ejaculatory dysfunction, reported in 186 (22%) patients in the silodosin group and six (0.9%) in the placebo group (odds ratio 28.14; P < 0.001). Dizziness and orthostatic hypotension rates were similar in silodosin and placebo groups. Conclusions Silodosin is an effective treatment for male lower urinary tract symptoms suggestive of benign prostatic hyperplasia. The drug is able to improve total IPSS, all IPSS‐related parameters, and Qmax at uroflowmetry. Ejaculatory dysfunction is the main treatment‐related AE, whereas prevalence of cardiovascular AEs was similar to placebo.